2019
DOI: 10.1016/j.geomorph.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Continental slope-confined canyons in the Pearl River Mouth Basin in the South China Sea dominated by erosion, 2004–2018

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
1
13
1
Order By: Relevance
“…Pioneering works, based on fixed morphology through seismic J o u r n a l P r e -p r o o f profiles (Hay, 1987) and sediment cores (Nesteroff and Heezen, 1962), allow the good understanding of different canyon types and their functioning. Over the last 20 years, current meter and sediment trap moorings (Xu et al, 2002;Khripounoff et al, 2003;Paull et al, 2002;Lintern et al, 2016;Zhang et al, 2018), repeated bathymetric surveys (Smith et al, 2005(Smith et al, , 2007Xu et al, 2008;;Hughes Clarke et al, 2014;Lintern et al, 2016;Hage et al, 2018;Yin et al, 2019) and direct observation by ROV (Gillet et al, 2019;Paull et al, 2005;Paull et al, 2010) have contributed to filling the gap between observed morpho-sedimentary features and hydro-sedimentary processes. The monitoring of currents and of seabed morphology of both active canyons that are significantly supplied by sediment during the present high-stand (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering works, based on fixed morphology through seismic J o u r n a l P r e -p r o o f profiles (Hay, 1987) and sediment cores (Nesteroff and Heezen, 1962), allow the good understanding of different canyon types and their functioning. Over the last 20 years, current meter and sediment trap moorings (Xu et al, 2002;Khripounoff et al, 2003;Paull et al, 2002;Lintern et al, 2016;Zhang et al, 2018), repeated bathymetric surveys (Smith et al, 2005(Smith et al, , 2007Xu et al, 2008;;Hughes Clarke et al, 2014;Lintern et al, 2016;Hage et al, 2018;Yin et al, 2019) and direct observation by ROV (Gillet et al, 2019;Paull et al, 2005;Paull et al, 2010) have contributed to filling the gap between observed morpho-sedimentary features and hydro-sedimentary processes. The monitoring of currents and of seabed morphology of both active canyons that are significantly supplied by sediment during the present high-stand (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a clear asymmetry in the sub-linear, slope-confined canyons of the Pearl River Mouth Basin, as shown by their steep eastern walls and stepped, curved western walls sculpted by slumps and slides (Ding et al, 2013;He et al, 2014). Yin et al (2019) link the asymmetry of these submarine canyons to contour currents, as well as to turbidity currents.…”
Section: Introductionmentioning
confidence: 88%
“…Smith et al, 2018), slope currents (e.g. Wang et al, 2018), high-energetic waves (e.g., solitary waves, Yin et al, 2019;storm waves, Sequeiros et al, 2019), and dense shelfwater cascading (e.g. Canals et al, 2006;Puig et al, 2014 and references therein;Gales et al, 2021).…”
Section: Hydrodynamic Processesmentioning
confidence: 99%
“…Slope-confined canyons can be fed by sands overpassing the shelf edge if their heads are in the range of the run-out distance of turbidity currents linked to fluvial discharge or littoral cells (e.g. Cronin et al, 2005;Yin et al, 2019). Canyons in high-latitude settings affected by glaciation can receive sediment delivered by the progradation of ice sheets onto shelf margins and from floating ice carrying debris (e.g.…”
Section: Interpretationsmentioning
confidence: 99%